2018
DOI: 10.4103/jehp.jehp_34_17
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C: Knowledge and awareness of private dental practitioners of a tricity in India

Abstract: BACKGROUND:Dental health-care personnel are at an increased risk toward infections caused by various microorganisms including hepatitis B and hepatitis C viruses (HCV). A dentist can play an important role in the prevention of HCV by considering every patient as a potential carrier for hepatitis. Therefore, the present study was conducted to assess the knowledge and awareness of dental health-care professionals regarding various aspects of HCV.MATERIALS AND METHODS:A cross-sectional study was conducted among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
2
14
2
1
Order By: Relevance
“…About 41.5% participants answered that HCV vaccine is available, whereas in reality no viable vaccine against HCV exists at present. Almost similar result has been reported by Peeran et al 2 and Setia et al 18 but the study done by Sharma et al, Gambhir RS et al, 19 74.4% and 53% participants respectively agreed for the presence of vaccine. And in studies by Rostamzadeh et al, 20 Kadeh 21 and Batool et al 17 about 66%, 8% and 25% dentists respectively had agreed for the presence of vaccine.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…About 41.5% participants answered that HCV vaccine is available, whereas in reality no viable vaccine against HCV exists at present. Almost similar result has been reported by Peeran et al 2 and Setia et al 18 but the study done by Sharma et al, Gambhir RS et al, 19 74.4% and 53% participants respectively agreed for the presence of vaccine. And in studies by Rostamzadeh et al, 20 Kadeh 21 and Batool et al 17 about 66%, 8% and 25% dentists respectively had agreed for the presence of vaccine.…”
Section: Discussionsupporting
confidence: 83%
“…About 81.6% dental interns felt they should uphold the confidentiality of their patients as compared to the lower percentage (66.7%) of dental interns in study by Peeran et al 2 Only 61.9% of participants in the present study had good knowledge scores regarding HCV. This finding is better than other studies conducted by Todorova 16 et al, Gambir 19 et al, Peeran 2 et al where only 6%, 21% and 45% had good knowledge respectively. There was relationship between Gender and mean knowledge scores in present study, with higher knowledge among females.…”
Section: Discussioncontrasting
confidence: 66%
“…The most commonly used preliminary impression material in this survey was impression compound (78%); irreversible hydrocolloid was used by only 20% [ (Kakatkar, 2012)]. Another survey of four major Indian cities showed that a majority (71%) use alginate for preliminary impressions [ (Gambhir et al, 2018)]. Similar findings have been reported in a survey of practitioners in the United Kingdom [ (Hyde, Paul Hyde and Fraser McCord, 1999)].…”
Section: Discussion :-supporting
confidence: 73%
“…Pakistan ( 34 ), Poland ( 35 ), India ( 36 ), and Iran ( 37 ) have reported the knowledge and attitudes about hepatitis virus among dentists. In Poland, a survey of 192 dentists revealed that a relatively high percentage (25%) refused to provide services to infected patients with HBV, HCV and HIV due to concerns about their health ( 35 ).…”
Section: Dental Care and Viral Hepatitismentioning
confidence: 99%
“…In Poland, a survey of 192 dentists revealed that a relatively high percentage (25%) refused to provide services to infected patients with HBV, HCV and HIV due to concerns about their health ( 35 ). A cross-sectional study conducted in India to assess the knowledge and awareness about HCV among dental health-care professionals found a statistically significant association between mean knowledge scores and gender, education level, and experience ( 36 ). A cross-sectional study from Iran showed that the knowledge, attitudes, and practices (KAP) of dentists with regard to HBV, HCV, and HIV were influenced by their age, work experience, and year of graduation ( 37 ).…”
Section: Dental Care and Viral Hepatitismentioning
confidence: 99%